Cartels and Casinos: First Nations’ Gaming in Canada ... - Flanagan, Tom (Fraser Institute, 2020)
In 1985, Parliament amended the Criminal Code to give the provinces jurisdiction over gambling. The provinces have used their new jurisdiction to create cartels for their own profit, in which they are either the owners of licensed casinos or take a large share of the profit. First Nations challenged the provinces in court but lost. Hence, they have had to fit into the cartel system and take leftovers—with a few exceptions, casinos located far from the main action. Only Alberta has let them into lucrative metropolitan markets, with one casino each in Edmonton and Calgary. Saskatchewan and Manitoba have recently licensed First Nation casinos not too far from Saskatoon and Winnipeg. In Ontario, Casino Rama is in a popular resort location, and the Membertou VLT parlours are situated within the small city of Sydney, Nova Scotia.Obviously a lot of money moves around in casinos, but does it benefit the host First Nations? The answer is an emphatic “Yes” for the half-dozen casinos located in or near cities and ...